Psychiatric Morbidity among a Sample of Orphanage Children in Cairo - Mohamed A. EL Koumi; Yasser F. Ali; Ehab A. El Banna; Usama M. Youssef; Yasser M. Raya; Aly A. Ismail (International Journal of Pediatrics)
Objective. This study identifies the prevalence of emotional and behavioral problems and the associated factors in orphanage children. Methods. This cross-sectional study was conducted in three private orphanages in Cairo. Two hundred sixty-five children of ages ranging from 6 to 12 years living in three different orphanages care systems were included in the study. A sociodemographic information form and the Child Behavior Checklist (CBCL) were used. Children were clinically interviewed and psychiatric disorders were identified. Diagnoses were done according to the manual for diagnosis and statistics of mental disorder fourth version (DSMIV). A written formal consent from the director of social solidarity was obtained before inclusion in the study. Results. The prevalence of behavioral disturbances was 64.53% among those in institutional care and the most prominent psychiatric disorders were nocturnal enuresis (23.3%), attention deficit hyperkinetic disorder (ADHD) (19.62%), oppositional defiant disorder (17.36%). Age at first admission, causes of receiving institutional care, and moves 2 or more times between institutions were significantly associated with an increased risk of behavioral and emotional problems. Conclusion. Our study showed that children living in institutions are prone to suffer from psychiatric disorders. Stability of the caregiver acts as a protective variable.